Fascynacje. Peter Brook* - CZOP, IRENEUSZ (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Fascinations. Peter Brook The author analyses various aspects of acting in the context of Peter Brooks theory of acting. This discussion takes into account role construction, the authenticity and originality of the character, the problem of the actors identification with the character and the importance of cooperation between the actor and the director in the pre-production process and on the shoot.